2021
DOI: 10.1186/s12888-021-03222-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a digital alcohol moderation intervention as an add-on to depression treatment for young adults: study protocol of a multicentre pragmatic randomized controlled trial

Abstract: Background Depressive disorders and problematic drinking often co-occur, also among young adults. These co-occurring conditions are associated with various negative health outcomes compared to both conditions alone. Early intervention by addressing alcohol use and depressive symptoms simultaneously in the same treatment might improve both conditions. However, evidence on the (cost-) effectiveness of digital combined depression and alcohol interventions for young adults is currently insufficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…1 ). A detailed overview of the content and features of the final digital intervention has been published elsewhere ( Schouten et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). A detailed overview of the content and features of the final digital intervention has been published elsewhere ( Schouten et al, 2021 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…This qualitative study was conducted to inform the development of a novel add-on digital alcohol intervention to complement depression treatment for young adults with co-occurring depression and problematic alcohol use. The development of the digital alcohol intervention was part of a larger study in which we aimed to develop and evaluate the (cost-)effectiveness of this digital alcohol intervention for depression treatment ( Schouten et al, 2021 ). The randomized controlled trial protocol and detailed overview of the content and features of the final digital intervention have been published elsewhere ( Schouten et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review also concluded there needs to be higher understanding of the (cost-)effectiveness of digital psychological interventions [80]. A randomized controlled trial is currently partly evaluating the (cost-)effectiveness of a digital alcohol moderation intervention (web app based on motivational interviewing and CBT) which was added to an existing depression treatment for young adults [81].…”
Section: Digital Mental Health For Young Peoplementioning
confidence: 99%